Comparison of the Amount of Debris Extruding from the Apical in Teeth Using Nickel Titanium File Systems with Different Taper Angles with Rotation Movement - Önalan, Abdurrahman Can; Öztekin, Faruk (Harran Üniversitesi, 2022)
Background: The aim of this study is to compare the amounts of debris extruding from apical of nickel titanium file systems with different taper angles that make rotation movement. Materials and Methods: Sixty mandibular premolar, round, never having had endodontic treatment before, nonfractured teeth, the apex of which were fully formed, having a root canal were selected. Care was taken so as to ensure that the selected teeth were of similar length and dimensions. It was confirmed that the teeth have round, singlerooted, non-resorption and having straight canals according to the radiographs from mesiodistal and buccolingual directions. The One-way Anova test was used so as to determine if there was any difference in the amount of debris extruded with respect to the varying taper angles of the file system. The Bonferroni test was used as the Post Hoc test for the paired comparison of the groups. Results: According to the results obtained, there is a statistically significant difference in the amount of extruded debris between the groups (F=469,279; p<0, 05). Conclusions: It was determined that while the weight of the extruded debris amount was at the file with the highest 0.6 taper angle (0.031±0.003), it was lowest at the file with a taper angle of 0.2 (0.008±0.002).
Keywords: Dentistry; Diş Hekimliği